The quality cure : how focusing on health care quality can save your life and lower spending too - Cutler, David M. (Berkeley : University of California Press, 2014)
"In the United States, the soaring cost of health care has become an economic drag and a political flashpoint. Moreover, although the country's medical spending is higher than that of any other nation, health outcomes are no better than elsewhere, and in some cases are even worse. In The Quality Cure, renowned health care economist and former Obama advisor David Cutler offers an accessible and incisive account of the issues and their causes, as well as a road map for the future of health care reform -- one that shows how information technology, realigned payment systems, and value-focused organizations together have the power to resolve this seemingly intractable problem and transform the US health care system into one that is affordable, efficient, and effective."--Provided by publisher
Cost, Access, and Quality: The Three Horsemen of the Apocalypse -- The Value Proposition -- The Cost Control Debate -- The Quality Cure -- It's What You Know -- Pricing the Priceless -- Take Me to Your Leader -- How Long Will It Take?
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Medical care; Medical care -- Quality control; Outcome assessment (Medical care); Cost control; Delivery of Health Care -- economics; Quality of Health Care; Cost Control; United States; Quality Assurance, Health Care; Outcome and Process Assessment, Health Care; Treatment Outcome; Outcome Assessment, Health Care; Patient Care; Soins médicaux -- Qualité -- Contrôle.; Évaluation des résultats (Soins médicaux); Coût -- Contrôle.; Soins médicaux.; cost control; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Disease & Health Issues; Cost control; Medical care; Medical care -- Quality control; Outcome assessment (Medical care)